(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the influence of problematic social media use on nomophobia among adolescents. This research uses a quantitative approach with a correlational design. The sampling technique used purposive sampling of 378 samples aged 15-17 years. The research instrument consists of two scales: the Problematic Social Media Use scale and the Nomophobia scale. The data analysis technique used is simple linear regression. Based on the research findings, it revealed that problematic social media use significantly influences nomophobia, with a coefficient of determination (R²) of 0.609. Additionally, the relationship between the two variables is classified as strong, with a correlation coefficient (r) of 0.781. The significance test results indicated a p-value of 0.000 (p < 0.05).